EPIZOOTIC ANALYSIS OF THE PREVALENCE OF TREMATODOSES (American Journal of Pedagogical and Educational Research, 2023)
This article presents information collected in the literature on the distribution of trematode infections in animals in Central Asia, Russia, Europe, Africa, and America. Also carried out was an analysis of the economic damage caused by this parasitic disease.